Analisis Kesalahan Siswa dalam Menyelesaikan Soal Logaritma Dasar Berdasarkan Teori Kastolan - Hidayah, Shofia (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2023)
This research is qualitative and aims to describe students' mistakes in solving logarithmic problems based on the Castolan theory. The types of errors in this study are classified into three types: conceptual errors, procedural errors, and technical errors. The subjects in this study were 20 students of class XI of IPA MA Nurul Jadid Paiton Probolinggo. The instrument used in this study is the instrument test questions. The test questions used consisted of five questions in the form of descriptions. The conclusion of this study is that the percentage of errors in class XI IPA MA Nurul Jadid in solving logarithmic questions for conceptual errors is 53%, procedural errors are 31%, and technical errors are 16%. The type of conceptual error that students make in solving test questions that is most prevalent is that they tend to deviate from the formula that applies to logarithms. This happens because students do not fully understand the properties that apply to logarithms. Types of procedural errors made by students in solving test questions, namely students not completing the steps of working on the questions so that the answers obtained are incomplete. Types of technical errors made by students in solving test questions include student errors in the calculation process. Students tend to be less careful when doing calculations, so the final answer obtained is not quite right.